Biodiversity and Structural Analysis of Woody Plant Species of Home Gardens in Basona Worana District, North Shoa Zone of Central Ethiopia - Almaz Woldeyohannes; Admasu Moges (Scientifica)
The purpose of this study was to investigate the biodiversity and structure of woody plants of HGs in the Basona Worana district (BWD). For this, six kebeles and 138 HGs from three agroecologies of BWD were selected using various sampling techniques. The plot size used per HG was 400 m2. Diversity and important value indices (IVIs) were computed. For their structural analysis, the diameter at breast height (DBH) and height were also measured for trees and shrubs fulfilling the standards (diameters at breast height (DBH) ≥2.5 cm and height >2 m). Thus, a total of 42 woody species belonging to 37 genera and 26 families were identified. Fabaceae was the most abundant family, followed by Euphorbiaceae. Trees were the dominant habit. The richness in Kola HGs (33) was higher than Dega (14) and Woinadega (19) HGs, with an overall mean richness of 4.14 per HG of BWD. The Shannon, Simpson, and evenness indices for HGs in the district were 1.05, 0.55, and 0.75, respectively, showing their moderate diversity with even distribution. The Sorenson’s similarity of HGs between Dega and Woinadega, Kola and Dega, and Kola and Woinadega were 40%, 28%, and 32%, respectively. The multiple site similarities of woody species among three ecological zones (36%) were still <50%, showing no similarity. The overall DBH and height classes’ patterns of the woody species individuals abruptly decreased towards their highest classes. Similar DBH and height classes’ patterns of woody species individuals were also observed in Kola and Woinadega agroecologies, indicating their selective tree cutting. The mean values of DBH, height, basal, and crown areas of the woody species in the district were ∼14 cm, ∼6 m, ∼29 m2·ha−1, and 5 m2, respectively. Based on IVI, most of the HGs were dominated by Eucalyptus globules (93.35), followed by Eucalyptus camaldulensis (45.04), Rhamnus prinoides (22.4), and Cupressus lusitanica (22.33). Hence, actions should be taken to promote the diversity and managing of HGs’ woody species of BWD.